2019
DOI: 10.1002/jbt.22311
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N‐acetylcysteine supplementation on the oxidative stress levels, apoptosis, DNA damage, and hematopoietic effect in pesticide‐exposed fish blood

Abstract: Cysteine is important for protein synthesis, detoxification, and diverse metabolic functions.However, cysteine metabolism has been poorly described in fish, and the role of the therapeutic effect in pesticide toxicology on aquatic organisms is unknown. The aim of this study was to determine the effects of regular cysteine treatment on the hematology, biochemistry, apoptosis, oxidative DNA damage, and antioxidant parameters in fish blood after chemical application. Therefore, fish were exposed to cypermethrin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
4
3
0
1
Order By: Relevance
“…The increase in the activities of ALT, AST, and LDH can be caused by damage to the liver tissue as a result of the toxic effects of pesticides, as well as some diseases (Bhardwaj et al 2010, Vahedi et al 2017, Ucar et al 2019. In this study, statistically significant increases were observed in serum levels of AST, ALT, and LDH at all times of exposure to tebuconazole (24, 48, 72, and 96 h).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The increase in the activities of ALT, AST, and LDH can be caused by damage to the liver tissue as a result of the toxic effects of pesticides, as well as some diseases (Bhardwaj et al 2010, Vahedi et al 2017, Ucar et al 2019. In this study, statistically significant increases were observed in serum levels of AST, ALT, and LDH at all times of exposure to tebuconazole (24, 48, 72, and 96 h).…”
Section: Discussionsupporting
confidence: 51%
“…Blood indices of fish exposed to toxic substances are commonly used as bioindicators. The decrease in hemoglobin, an indicator of anemic conditions, can be considered to be the result of hemolysis caused by stress caused by toxic substances (Ucar et al 2019). The erythrocyte numbers, Hb content, and Hct levels decrease in fish exposed to toxic substances may be due to inhibition of erythrocyte synthesis (Özok et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the bacterial application caused the red cells to shrink (increased MCHC), and MCH increased significantly. It had been reported that high MCHC and MCH values indicate the presence of large-sized RBCs with lower hemoglobin content (Ucar et al 2019;Alak et al 2020b;Ucar et al 2021). In our study, we believe that the anemic condition is effective in increasing MCV and MCH levels in fish exposed to different bacterial strains.…”
Section: Tissues Treatmentsupporting
confidence: 59%
“…According to Mani et al [21], zebrafish (Danio rerio) exposed to 1 and 3 mg/L presented a significant increase in serum CK activity, a condition that is considered to be an indicator of tissue damage and which was confirmed due to elevated levels of tissue ROS and oxidative stress. A study conducted by Ucar et al [22] confirmed that CK (total CK) and CK-MB were significantly higher in rainbow trout (Oncorhynchus mykiss) exposed to 2.05 ug/L cypermethrin pesticide for 96 h compared to the control fish. This is a condition compatible with tissue damage in general, as well as to heart damage due to elevated CK-MB activity.…”
Section: Creatine Kinase As An Indicator Of Damagementioning
confidence: 91%
“…Exposure to polyethylene microplastic Plasma Increase in CK activity [19] Labeo rohita Exposure to decabromodiphenyl ether Serum Increase in CK activity [20] Danio rerio Exposure to copper oxide nanoparticles Serum Increase in CK activity [21] Oncorhynchus mykiss Exposure to cypermethrin Serum Increase in CK and CK-MB activities [22] Oncorhynchus mykiss Bacterial infection (Flavobacterium psychrophilum) Serum Increase in CK activity [23] Oncorhynchus nerka Exposure to bitumen Serum Increase in CK activity [24] Scophthalmus maximus Thermal stress Plasma Increase in CK activity [25] Oreochromis niloticus Water pollution Serum Increase in CK activity [26] 2.1. Creatine Kinase as an Indicator of the Negative Effects on Energetic Homeostasis in Fish during Bacterial, Fungal, and Parasitical Infections Bacterial, fungal, and parasitical diseases are recognized as the main impediments of aquaculture development, causing severe economic impairments to fish farming and contributing to the development of antimicrobial resistance and environmental contamination due to the excessive use of drugs to combat these infections [27,28].…”
Section: Cyprinus Carpiomentioning
confidence: 99%